2024
DOI: 10.1111/jcmm.18394
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of CDKN2A in head and neck squamous cell carcinoma via pathomics and machine learning

Yandan Wang,
Chaoqun Zhou,
Tian Li
et al.

Abstract: This study aims to enhance the prognosis prediction of Head and Neck Squamous Cell Carcinoma (HNSCC) by employing artificial intelligence (AI) to analyse CDKN2A gene expression from pathology images, directly correlating with patient outcomes. Our approach introduces a novel AI‐driven pathomics framework, delineating a more precise relationship between CDKN2A expression and survival rates compared to previous studies. Utilizing 475 HNSCC cases from the TCGA database, we stratified patients into high‐risk and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In addition, other genes, such as CEACAM6, play a major role in tumor growth, and chemotherapeutic sensitivity has been assessed both in vivo and in vitro (Cameron et al, 2012). Furthermore, Wang et al (2024) reported a direct correlation between the expression levels of the CDKN2A gene and patient outcomes. CDKN2A gene is a crucial prognostic marker in HNSCC, serving to establish enhanced and personalized therapeutic targets and also involved in cell cycle progression.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other genes, such as CEACAM6, play a major role in tumor growth, and chemotherapeutic sensitivity has been assessed both in vivo and in vitro (Cameron et al, 2012). Furthermore, Wang et al (2024) reported a direct correlation between the expression levels of the CDKN2A gene and patient outcomes. CDKN2A gene is a crucial prognostic marker in HNSCC, serving to establish enhanced and personalized therapeutic targets and also involved in cell cycle progression.…”
Section: Introductionmentioning
confidence: 99%